2015
DOI: 10.3233/jad-142910
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cognitive Decline Prior to Dementia in Persons with Mild Cognitive Impairment

Abstract: Only a limited number of studies have investigated the decline of discrete cognitive domains as individuals progress from mild cognitive impairment (MCI) to dementia. Thus, the goal of this longitudinal study was to evaluate the cognitive changes underway during the years preceding a diagnosis of probable Alzheimer’s disease (AD), and to compare these changes to those found in MCI participants who do not progress to dementia. Participants were compared as a function of whether they later converted to AD (n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 51 publications
2
63
0
Order By: Relevance
“…While some of our more influential predictors are similar to those identified by studies of conversion, risk factors for conversion such as education, sex, ethnicity, MCI subtype, and executive function (Campbell et al, 2013; Cloutier et al, 2015; Lee et al, 2012; Ye et al, 2013; Yoon et al, 2015) did not appear to be influential in predicting MCI stability in our overall predictive model. Further, we found that cardiovascular risk factors did not distinguish MCI-stable individuals from converters, indicating that vascular burden does not significantly affect MCI stability over 3 years.…”
Section: Discussionsupporting
confidence: 58%
“…While some of our more influential predictors are similar to those identified by studies of conversion, risk factors for conversion such as education, sex, ethnicity, MCI subtype, and executive function (Campbell et al, 2013; Cloutier et al, 2015; Lee et al, 2012; Ye et al, 2013; Yoon et al, 2015) did not appear to be influential in predicting MCI stability in our overall predictive model. Further, we found that cardiovascular risk factors did not distinguish MCI-stable individuals from converters, indicating that vascular burden does not significantly affect MCI stability over 3 years.…”
Section: Discussionsupporting
confidence: 58%
“…The value of using a broad-based test battery with language performance measures, as well as measures of other key cognitive abilities, as recommended by the NIA-AA MCI workgroup (Albert et al, 2011) and the American Psychiatric Association (2013), cannot be overstated. As previously noted, many etiologies are associated with MCI and can present with deficits other than memory or language impairment, for example, visual spatial impairment (Cloutier, Chertkow, Kergoat, Gauthier, & Belleville, 2015;Fujimori et al, 1998;Possin, 2010).…”
Section: Value Of Broad-based Standardized Batterymentioning
confidence: 92%
“…Although it was clear that the cognitive markers were better predictors of dementia closer to diagnosis, the relative importance among the predictors did not appear to substantially change over time. It has been shown that the rate of cognitive decline in the preclinical phase differ across cognitive domains (Cloutier et al, 2015;Grober et al, 2008;Thorvaldsson et al, 2011), suggesting that different domains may be more or less useful for predicting future dementia depending on time until diagnosis. However, using the scores from single points in time (as opposed to investigating rate of decline), this study rather points to the same domains being the most predictive of future dementia.…”
Section: Time-to-diagnosismentioning
confidence: 99%
“…Longitudinal studies mapping rates of decline suggest that some cognitive domains start to decline earlier and some later in relation to the dementia diagnosis, and they may follow different trajectories (Cloutier, Chertkow, Kergoat, Gauthier, & Belleville, 2015). Thus, different cognitive domains may be more or less useful in predicting future dementia depending on time to diagnosis.…”
Section: Introductionmentioning
confidence: 99%